Resúmenes de novedades - Foro Internacional, Revista (Foro Internacional, 2024)
ANTONY LOEWENSTEIN, The Palestine Laboratory: How Israel Exports the Technology of Occupation Around the World, Nueva York, Verso, 2023, 304 pp. SILJA HÄUSERMANN y HERBERT KITSCHELT (eds.), Beyond Social Democracy: The Transformation of the Left in Emerging Knowledge Societies, Cambridge, Reino Unido, Cambridge University Press, 2024, 488 pp. DEREK BOK, Attacking the Elites: What Critics Get Wrong—and Right—About America’s Leading Universities, New Haven, Yale University Press, 2024, 248 pp. ELŻBIETA DRĄŻKIEWICZ y JARON HARAMBAM (eds.), What to Do About Conspiracy Theories? Academic Entanglements in Conflicts Over Truths, Nueva York, Routledge, 2024, 122 pp. DANA R. FISHER, Saving Ourselves: From Climate Shocks to Climate Action, Nueva York, Columbia University Press, 2023, 250 pp. VALERIE FREELAND, Power, Patronage and International Norms: A Grand Masquerade, Cambridge, Reino Unido, Cambridge University Press, 2024, 298 pp. ANDRÉ BORGES, RYAN LLOYD y GABRIEL VOMMARO (eds.), The Recasting of the Latin American Right: Polarization and Conservative Reactions, Cambridge, Reino Unido, Cambridge University Press, 2024, 260 pp. ANA COVARRUBIAS, CARLA YUMATLE y JEAN-MARIE CHENOU (coords.), El mundo visto desde América Latina: una revisión de los conceptos básicos de las relaciones internacionales, Buenos Aires , Siglo XXI Editores, 2024, 327 pp. CLAUDIO LOMNITZ, Para una teología política del crimen organizado, Ciudad de México, Ediciones Era, 2023, 216 pp. MAURICIO MERINO, Gato por liebre. La importancia de las palabras en la deliberación pública, Barcelona, Debate, 2023, 200 pp.